STABILITAS EMOSI DAN IMPLIKASINYA PADA KESEJAHTERAAN PSIKOLOGIS - Amanda Nofriandini; Mutia Nabila Putri; Fadiah Cahyani; Mya Indrawati; Andini Oktary; Yorisa Rahmawati; Izzanil Hidayati (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to examine the relationship between emotional stability and psychological well-being in final year university students. College students are often faced with high academic pressure, which may affect their psychological well-being. Emotional stability, which refers to the ability to maintain emotional balance in the face of stress, is expected to contribute to better psychological well-being. This study used a cross-sectional survey design with 44 participants of Psychology students at Universitas Negeri Padang. Data were collected through emotional stability and psychological well-being scales, which were analyzed using Pearson correlation. The results showed a significant positive relationship between emotional stability and psychological well-being (r = 0.723, p = 0.000). These findings indicate that increasing emotional stability can improve students' psychological well-being, which is important for managing academic stress.